TUMPENG MEGANA AS A SOURCE OF IDEAS CREATION MOTIVE BATIK ON CLOTHES CASUAL - Arifah, Hesti Nur (Runtas : Journal Of Arts And Culture, 2023)
Abstract Tumpeng megana is a traditional Indonesian culinary served at the event thanksgiving birth baby or commemorate day born. Presentation tumpeng megana as form symbolic as a delivery of gratitude and supplication or pray. Characteristic features tumpeng megana is rice white form cone And surrounded side dish pauk And vegetables around the rice and there are sticks of eggs, shallots, and chilies on top of the rice. The rice white color which symbolizes a purity and vegetables which symbolize hope or prayer request in living life for the child someday, whereas the stab symbolize roundness embroidery Which full Spirit in face challenges in later life. The purpose of creating this work is to introduce back to the culinary archipelago that was almost lost amidst the incoming foreign culinary and develop in Indonesia. Poured into the exists work motive batik on fashion casual . Casual clothing is clothing that is suitable for everyday use and casual needs made with the comfort of the wearer in mind. The foundation of creation on the process The creation of this final project adheres to SP Gustami's creation method with 3 stages namely the exploration stage, the design stage, and the embodiment stage. Motive design selected with the source of ideas from tumpeng megana created through the process of batik and unplug color. Batik write is process incision Evening on cloth with use canting which aims to block the colors. In the process of making batik using dyes remasol And unplug color with use sulfurite.